Neurological Disorders and Clinical Progression in Boxers from the 20th Century: A Narrative Review - Rudolph J. Castellani; Nicolas Kostelecky; Jared T. Ahrendsen; Malik Nassan; Pouya Jamshidi; Grant L. Iverson (Brain Sciences)
Introduction: There are no validated clinical diagnostic criteria for chronic traumatic encephalopathy or traumatic encephalopathy syndrome (TES). To understand the historical clinical condition, its applicability to modern day athletes, and the pathogenesis of clinical problems, we examined the literature describing boxers from the 20th century, with specific attention paid to neurological findings and characteristics of clinical disease progression. Methods: Data were extracted for 243 boxers included in 45 articles published between 1928 and 1999, including cases from articles originally published in German. The presence or absence of 22 neurological signs and features were extracted. Results: The most common neurological problems were slurring dysarthria (49%), gait disturbances (44%), and memory loss (36%), with several other problems that were less frequent, including hyperreflexia (25%), ataxia (22%), increased tone (19%), and extensor Babinski sign (16%). Frank dementia appeared in some cases (17%). There were significantly fewer neurological deficits reported in boxers who fought in the latter part of the 20th century compared to boxers who fought earlier in the century. For more than half of the cases, there were no comments about whether the neurological problems were progressive (145, 60%). A progressive condition was described in 71 cases (29%) and a stationary or improving condition was described in 27 cases (11%). Canonical neurodegenerative disease-like progression was described in 15 cases (6%). Discussion: Neurological problems associated with boxing-related neurotrauma during the 20th century are the foundation for present-day TES. However, the clinical signs and features in the 20th century differ in most ways from the modern criteria for TES.